ANALISIS POTENSI DESTINASI WISATA PASAR MODERN SUMMARECON BANDUNG SEBAGAI PARIWISATA RAMAH MUSLIM (PRM) - Ramdani, Dadan (PUSLITABMAS - BATAM TOURISM POLYTECNIC, 2025)
Halal tourism is a rapidly growing sector globally, with Muslim tourist trips projected to reach 230 million by 2028, according to the 2023 Global Muslim Travel Index (GMTI). Indonesia, as a predominantly Muslim country, has significant potential to develop halal-compliant tourist destinations, including West Java, which boasts rich tourism potential. One such destination is the Summarecon Modern Market, renowned for its beauty and uniqueness. This study aims to analyse the potential of the Summarecon Modern Market as a halal tourism destination based on four GMTI indicators: accessibility, communication, environment, and services. The research method used was a descriptive qualitative case study approach, where data were collected through in-depth interviews with managers, tourists, and vendors, as well as direct on-site observation. The results indicate that the Summarecon Modern Market excels in accessibility with easy transportation and ample parking facilities, a clean environment, and friendly and responsive service. However, there are still shortcomings in the communication of halal information, which has not been communicated strategically, and the low number of vendors with halal certification. Based on these findings, strengthening halal literacy among business actors, improving public information regarding halal facilities, and implementing halal certification assistance programs are needed to enhance the competitiveness of Summarecon Modern Market in the national and global halal tourism markets.